1999
DOI: 10.1093/ajcn/69.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Threonine kinetics in preterm infants fed their mothers' milk or formula with various ratios of whey to casein

Abstract: Background: Plasma threonine concentrations are elevated in infants fed formula containing a whey-to-casein protein ratio of 60:40 compared with concentrations in infants fed formula containing a ratio of 20:80 or human milk (60:40). Objective: We studied whether degradation of excess threonine was lower in formula-fed infants than in infants fed their mothers' milk. Design: Threonine kinetics were examined in 17 preterm infants (gestational age: 31 ± 2 wk; birth weight: 1720 ± 330 g) by using an 18-h oral inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 43 publications
6
58
1
2
Order By: Relevance
“…One possibility is that threonine is being converted to glycine. In humans, the TDH pathway accounts for only 7-11% of threonine oxidation [16] in adults whereas up to 44% of oxidation is through this pathway in preterm infants [24]. Glycine is also important during gestation in rodents [25] and even a small increase in the conversion of threonine to glycine may lead to a considerable increase in the demand because of the high glycine flux.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that threonine is being converted to glycine. In humans, the TDH pathway accounts for only 7-11% of threonine oxidation [16] in adults whereas up to 44% of oxidation is through this pathway in preterm infants [24]. Glycine is also important during gestation in rodents [25] and even a small increase in the conversion of threonine to glycine may lead to a considerable increase in the demand because of the high glycine flux.…”
Section: Discussionmentioning
confidence: 99%
“…Cofactors include pyridoxal (vitamin B6, or nicotinamide adenine dinucleontide) and co-enzyme A. * Denotes the fate of the labelled carbon of L-(1-13 C)threonine through the degradative pathways (Bird and Nunn, 1983;Darling et al, 1999).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Earlier we published a study in which we showed that formula-fed preterm infants did not increase threonine degradation in response to increased threonine intake (8). Conversely infants fed their mother's own milk increased their oxidation of threonine and thereby could handle the relatively high load of threonine present in human milk protein (8). Since casein-dominant formulas are known to cause elevations in plasma phenylalanine and tyrosine levels (6,9,10) we decided to also investigate the ability of preterm neonates to handle an increased load of phenylalanine and tyrosine and compare the results with infants fed their mother's own milk.…”
mentioning
confidence: 98%
“…The initial approach was to produce infant formulas based on a whey:casein ratio of 60:40, approximating that in human milk, but this resulted in infants with high plasma threonine levels (6). Earlier we published a study in which we showed that formula-fed preterm infants did not increase threonine degradation in response to increased threonine intake (8). Conversely infants fed their mother's own milk increased their oxidation of threonine and thereby could handle the relatively high load of threonine present in human milk protein (8).…”
mentioning
confidence: 98%
See 1 more Smart Citation